2008
DOI: 10.1167/iovs.07-1126
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-wide Scan Maps a Novel High Myopia Locus to 5p15

Abstract: A novel autosomal dominant high myopia locus was mapped on chromosome 5p15.33-p15.2 with an interval of 17.45 cM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…27 This locus was further supported by an additional genome-wide linkage scan of Asian families. 37 Recently, a GWAS study on Singapore Chinese revealed that genetic variations in the noncoding region of CTNND2, the SNPs rs6885224 and rs12716080, were associated with high myopia.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…27 This locus was further supported by an additional genome-wide linkage scan of Asian families. 37 Recently, a GWAS study on Singapore Chinese revealed that genetic variations in the noncoding region of CTNND2, the SNPs rs6885224 and rs12716080, were associated with high myopia.…”
Section: Discussionmentioning
confidence: 76%
“…27 Recently, a GWAS study identified a strong association between high myopia and genetic variations in CTNND2, 33 which is located inside the linkage interval of MYP16. It would be of interest to know whether this association can be replicated by independent studies.…”
mentioning
confidence: 99%
“…A genome-wide scan of 94 high myopia cases drawn from a Chinese population and the same number of control subjects using microsatellite markers refined by genotyping SNP markers revealed a location on chromosome 5p that had not been previously reported (61). A maximum LOD score of 4.8.1 was associated with the 5p15.3.3-p15.2.…”
Section: Other Myp Locimentioning
confidence: 77%
“…22 This gene encodes an adhesive junction-associated protein of the armadillo/beta-catenin superfamily and is implicated in brain and eye development and cancer formation. 10 Two SNPs (rs12716080 and rs6885224) of CTNND2 in the metaanalysis of Singaporean Chinese data sets were identified strong association with high myopia.…”
Section: Discussionmentioning
confidence: 99%